Hospital-Based Air-Borne and Surface-Borne Bacterial Pathogens and Their Antimicrobial Profiles in Wolaita Sodo, Southern Ethiopia - Madebo, Chemere; Haile, Admasu; Eticha, Temesgen; Solomon, Fithamlak (International Journal of Microbiology, 2022)
Background. It is well documented that hospital environments are the niche/reservoir of many clinically important microorganisms, including multidrug-resistant air-borne and surface-borne pathogens. This problem is the most pressing public health concern, particularly in developing countries like Ethiopia, due to its poor infection management system. This study was planned to detect air-borne and surface-borne bacterial pathogens and their antimicrobial resistance patterns in Wolaita Sodo University Comprehensive Hospital, Southern Ethiopia. Method. A laboratory-based cross-sectional study was conducted from May to July 2021. Swabbing and open-plate sample collection methods were used to collect specimens. Standard bacteriological techniques were used to isolate and identify bacterial pathogens. The Mueller-Hinton agar was used to detect the drug susceptibility pattern of bacteria by using the Kirby-Bauer disc diffusion method. Result. From a total of 323 samples tested, 118 (36.5%) showed the growth of bacteria. The detection rate of bacterial pathogens in the intensive care unit (35.4%) was higher than in operation theater. From the total of 118 bacterial isolates, 39.8%, 27.9%, 20.3%, and 11.5% of S. aureus, P. aeruginosa, Klebsiella pneumoniae, and E. coli, respectively, were surface-borne. Whereas 37%, 25%, 20.83, and 16.6% of S. aureus, P. aeruginosa, Klebsiella species, and E. coli, respectively, were air-borne. S. aureus showed a 19.04 to 80.9% range of antimicrobial resistance to different classes of antibiotics from surface specimens. A 12.5–100% range of antibiotic resistance levels was detected for all Gram-negative surface-borne bacterial pathogens. P. aeruginosa was 66.7%, 73.3%, and 73.3% resistant to gentamicin, chloramphenicol, and ceftriaxone, respectively. K. pneumoniae showed 75% and 87.5% resistance to ceftriaxone and ciprofloxacin, respectively, and a completely ampicillin-resistant E. coli was detected. From a total of 48 bacterial pathogens identified from surfaces in the intensive care unit, 34 (70.8%) developed multidrug resistance. Conclusion. A significant prevalence of surface-borne bacterial pathogens was detected. This study revealed that S. aureus, P. aeruginosa, K. pneumoniae, and E. coli were nosocomial infection concerns of the hospital, and this could be the reason for different types of hospital acquired infections in the study area. A high prevalence of MDR was detected in the most surface-borne bacterial isolates.